Winds of Change: A Neo-Design Approach to the Regeneration of Regions. (December 2021) - Garud, Raghu; Gehman, Joel; Karnøe, Peter
Among scholars, policy makers, and practitioners, there is considerable interest in the dynamics associated with regions, including their emergence, decline, and regeneration. Such interest is well justified given the role that regions play in contributing to social well-being at a variety of scales—from individuals to communities and even nation-states. In this article, we examine the processes that unfolded during the regeneration of a region in Denmark that was known for its competence in manufacturing equipment and is now known as a world leader in wind turbines. We highlight three mechanisms that led to the regeneration of this region: repurposing, experimentation, and collective learning. Based on these findings, we propose a neo-design approach to the regeneration of regions.